Tooth Loss and Prosthesis Replacement at El-Koms City - Hussein Abuzgyaia (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objective. Loss of at least one tooth disturbs the structural balance of the remaining natural teeth and may result in widening of proximal contacts, and other deformities.The proportion of full and partial edentulous people, as well as their prosthetic therapy, were investigated El-Koms city Methods. Patient demographics, the percentage of partial and completely edentulous patients, and their prosthetic treatment were collected at four dental clinics. Health services. Ministry of Health in El-Koms city. The study was approved by the prosthodontics department, Faculty of Dentistry, University of Al Marqab. In 2020, a total of 1000 people were assessed in four dental clinics, with 472 individuals being chosen as part of the sample study group. Patients were chosen based on their age, which ranged from 25 to 75 years old, and their dental records.